Hubungan Antara Dukungan Orang Tua dengan Motivasi Akademik pada Siswa SMP X di Kota Bekasi - Rahma Meilina Arrazi; Mic Finanto Ario Bangun; Yulia Fitriani (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Academic motivation is a crucial factor that encourages students' engagement in the learning process and the achievement of academic goals. Low academic motivation may lead to reduced learning engagement, lower academic achievement, and an increased risk of academic stress. One external factor believed to be associated with academic motivation is parental support. This study aimed to examine the relationship between parental support and academic motivation among students at Junior High School X in Bekasi City. The study employed a quantitative correlational approach. The sample consisted of 143 seventh- and eighth-grade students selected using cluster random sampling. Data were collected using the Parental Support Scale based on Sarafino’stheory and the Academic Motivation Scale (AMS) adapted from Mangkading et al. Data were analyzed using the Pearson Product-Moment correlation test after meeting the assumptions of normality and linearity. Descriptive results indicated that most students had high academic motivation (97.20%) and high parental support (61.54%). This study is expected to contribute to a better understanding of the important role of parental support in enhancing students’ academic motivation.